Impaired functional responses in follicular lymphoma CD8+TIM-3+ T lymphocytes following TCR engagement. (2nd October 2016) - Gravelle, Pauline; Do, Catherine; Franchet, Camille; Mueller, Sabina; Oberic, Lucie; Ysebaert, Loïc; Larocca, Luigi Maria; Hohaus, Stefan; Calmels, Marie-Noëlle; Frenois, François-Xavier; Kridel, Robert; Gascoyne, Randy D.; et al.
ABSTRACT: Upregulation of T cell immunoglobulin-3 (TIM-3) has been associated with negative regulation of the immune response in chronic infection and cancer, including lymphoma. Here, we investigated the possible correlation between TIM-3 expression by ex vivo cytotoxic T cells (CTL) from follicular lymphoma (FL) biopsies and their functional unresponsiveness that could limit the favorable impact of CTL on disease progression. We report a high percentage of CD8 + TIM-3 + T cells in lymph nodes of FL patients. When compared to their CD8 + TIM-3 − counterparts, CD8 + TIM-3 + T cells exhibited defective cytokine production following TCR engagement. Furthermore, CD8 + TIM-3 + T cells display ex vivo markers of lytic granule release and remain unresponsive to further TCR-induced activation of the lytic machinery. Although confocal microscopy showed that TIM-3 expression on CD8 + T cells correlated with minor alterations of immunological synapse, a selective reduction of ERK signaling in CD8 + TIM-3 + T cells was observed by phospho-flow analysis. Finally, short relapse-free survival despite rituximab(R)-chemotherapy was observed in patients with high content of TIM-3 + cells and a poor infiltrate of granzyme B + T cells in FL lymph nodes. Together, our data indicate that, besides selective TCR early signaling defects, TIM-3 expression correlates with unresponsiveness of ex vivo CD8 + T cells in FL. They show that scores based on the combination of exhaustion and cytolytic markers in FL microenvironment might be instrumental to identify patients at early risk of relapses following R-chemotherapy.